PERAN PETANI PEREMPUAN DI PERKEBUNAN PALA KEPULAUAN BANDA TAHUN 1602-1799 - Rahma Temarwut (Universitas Banda Naira, 2026)
This study aims to explore women farmers in nutmeg plantations in the Banda Islands during the colonial period within the framework of historical studies. The study describes the concrete manifestations of women plantation workers during the colonial era and analyzes the roles of women in nutmeg plantations in the Banda Naira Islands. The method in this research is qualitative-historical, using a literature review approach and oral tradition. Data were collected through heuristics (source collecting) from written documents, images, and audio materials, as well as observation, interviews, documentation, and library-based literature studies, all aimed for understanding women farmers in nutmeg plantations in the Banda Islands during the colonial period. Oral tradition was also conducted within the Banda community to enrich this research. The findings reveal that during the colonial period, following the Genocide in 1621 against the Banda people, the majority of those who survived were exiled outside of Banda, a large number were Banda women. After the Genocide and the exile of the Banda people, the colonial authorities brought in forced laborers from outside Banda from Sulawesi, Java, and parts of Maluku. However, these incoming workers were not yet fully versed in the methods of processing nutmeg. As a result, the colonial authorities had no choice but to bring back the Banda women who had previously been exiled, so that they could carry out and teach the work of nutmeg processing in the plantations of the Banda Islands. The tasks performed by women nutmeg farmers during the colonial period included: harvesting or picking nutmeg fruit from the trees in the plantations, separating the nutmeg flower (mace) from the nutmeg fruit, sun-drying the nutmeg, and through to the process of selecting the finest quality nutmeg known as super (grade one) for trade. The Results of this study, it can be concluded that the role of Banda women during the colonial period was tremendously significant to the development of nutmeg plantations and trade, from the colonial era through to the present day.